Eksplorasi Peran Perbankan Syariah dalam Memajukan Industri Halal di Sektor Makanan Halal - Fatmawati Sungkawaningrum; Amin Nasrullah (SEKOLAH TINGGI AGAMA ISLAM AL-HUSAIN MAGELANG, 2019)
Indonesia has the most Muslim population in the world. This encourages Indonesian people to choose to live in sharia. Sharia is very closely related to the halal industri. Islamic banking can encourage halal industries in Indonesia. With the enthusiasm of the community to run a sharia system, it encourages banks to disburse financing to develop a halal industri. Global economic conditions have indicated and caught a signal that the Islamic economy began to develop. Halal industries should be developed in all sektors, but this sharia market share is not yet wide. The halal industri should be able to encourage the share of the Islamic banking market to develop broader Sharia-compliant goods and services. The research method used is descriptive quantitative method and literature review. From the results of the analysis of the role of banks, it is not limited to financing without training, guidance and usury, but also includes halal regulations, halal consumption of products, halal industri intelligence and lawful governance. The government has a role as a regulator between Islamic banking, business actors and MUI so that the economic potential and halal industri according to sharia can be realized